Islamic Business Ethics as Customer Retention Factors in Islamic Bank: an Exploratory Factor Analysis - Adib Susilo; Nurdianawati Irwani Abdullah; Nor Azizan Che Embi (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2022)
This study aims to explore the factors of Rasullah commendable qualities as partial variable in order to be able to test or examine that has been practiced by Islamic Bank employee at Ponorogo East Java Indonesia. Using 128 of respondents the data analyze quantitively. Data collected from respondent thorugh questionnaire responded on five point Likert scale. The data then analyzed employed Exploratory Factor Analysis (EFA) method using Varimax rotation, which reduced the data into several factors. The findings of this study indicates that commendable qualities of the Prophet Muhammad as business ethics indicators is emerged in 3 factors namely, siddiq, fathana, and tabligh, that probably would affect on costumer retention. Therefore, it is necessary future research to investigate the relationship 3 factors of commendable qualities of the Prophet Muhammad S.A.W. and customer retention in Islamic Bank especially in Ponorogo.